HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF - Andriani, Rezky; Rahman, Ulfiani; Nur, Fitriani; suharti, Suharti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Learning in the classroom cannot be separated from the application of the learning model, therefore the choice of a learning model is very important because it is related to the success of the teaching and learning process. The purpose of this research is to compare the mathematics learning outcomes of students using the Teams Geams Tournament (TGT) learning model with students using the cooperative learning model type Student Teams Achievement Division (STAD). This research is a quantitative non-equivalent control group design. The sample selection technique used was purposive sampling with the research instrument in the form of tests what were analyzed by inferential statistics and descriptive statistics. From the research result, it was found that there was no significant difference between student learning outcomes with the TGT and STAD learning models.